2016
DOI: 10.1111/jfq.12214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment with 1‐Methylcyclopropene and Clo2 on the Postharvest Shelf‐Life and Physiological Quality of Mulberry Fruit (Morus alba L.)

Abstract: In this paper, we examined the use of 1‐methylcyclopropene (1‐MCP) and ClO2 as safe and effective preservative agents for mulberries. Individual treatment of 1 g/m3 1‐MCP or ClO2 at 20 g/m3 significantly delayed fruit senescence and did not affect sensory qualities. Combined treatment of 1 g/m3 1‐MCP and 12 g/m3 ClO2 yielded the lowest mildew rate, and the fruits remained plump and bright with bright green stalks on the third day. In contrast, most of the mulberry fruits of the control group were moldy on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The TA contents of mulberries treated with 0.1 g/L and 0.3 g/L NA were 0.35% and 0.36% by 10 days, respectively. Previous studies have also reported that treatment of mulberries with 1‐MCP and ClO 2 (Fang et al, ), CaCl 2 (Oz & Ulukanli ), precooling (Han et al, ), and AITC (Chen et al, ) could effectively maintain TA contents throughout storage. The difference in TSS and TA contents between the control and NA‐treated mulberries could be explained by lowered respiratory rates (Figure ) and decay rates (Figure a).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The TA contents of mulberries treated with 0.1 g/L and 0.3 g/L NA were 0.35% and 0.36% by 10 days, respectively. Previous studies have also reported that treatment of mulberries with 1‐MCP and ClO 2 (Fang et al, ), CaCl 2 (Oz & Ulukanli ), precooling (Han et al, ), and AITC (Chen et al, ) could effectively maintain TA contents throughout storage. The difference in TSS and TA contents between the control and NA‐treated mulberries could be explained by lowered respiratory rates (Figure ) and decay rates (Figure a).…”
Section: Resultsmentioning
confidence: 93%
“…MDA levels in mulberries subject to treatment with 0.1 g/L and 0.3 g/L NA were 1.11 and 1.13 µmol/g, respectively, at 8 days, indicating that NA treatment could reduce MDA content of mulberry fruit. Previous studies have shown that AITC treatment (Chen et al, ), as well as the combined treatment of 1‐MCP and ClO 2 (Fang et al, ) could also decrease MDA content of mulberry fruit.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Further, mulberry fruit product consumption has been rapidly increasing because of biological benefits, nutritional value, and taste, (Aramwit et al, 2010), as cited by Raman et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Benzoic acid, chlorine dioxide, and 1-methylcyclopropene (1-MCP) are commonly used to prolong the shelf life of postharvest fruit and vegetables [ 11 , 12 , 13 ]. It is reported that preharvest application of benzoic acid can increase the content of total phenolic compounds and total anthocyanins in table grapes [ 14 ], and postharvest antimicrobial treatments with benzoic acid can improve the shelf life of fresh blueberries [ 15 ].…”
Section: Introductionmentioning
confidence: 99%